The Little Fog Dragon—a new genus of Mountain Lichen Katydid (Orthoptera: Tettigoniidae: Phaneropterinae: Dysoniini) from the Serra do Sol, Roraima, Brazil - de Mello Mendes, Diego Matheus (Zootaxa, 2022)
The Dysoniini tribe (Phaneropterinae: Tettigoniidae) currently comprises 15 genera and 85 species with a Neotropical distribution. The group is notable for its representatives possessing morphological adaptations to camouflage with lichens and fungi. In this work, the new genus Nebulodraculus gen. nov. is described with two species included: Nebulodraculus marioi sp. nov. (type species) and Nebulodraculus holgeri (Cadena-Castañeda, 2013) comb. nov. (transferred from Lichenodraculus Braun, 2011), known from mountainous environments in northern Brazil and Venezuela. Pictorial keys to the species of the genus, maps and natural history observations are provided.